2019
DOI: 10.7774/cevr.2019.8.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of standardized method for detecting immunogenicity of acellular pertussis vaccines in Korea

Abstract: PurposeThere is no standard method for confirming the immunogenicity of acellular pertussis vaccines. We tried to develop a local standard method for evaluating the immunogenicity of the three-component of acellular pertussis vaccines which was developed by a Korean local company.Materials and MethodsThe developed pertussis antigens (pertussis toxin, filamentous hemagglutinin, pertactin) were evaluated by in-house enzyme-linked immunosorbent assay (ELISA) using 189 negative sera, 25 positive sera, and 73 paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Thus, evaluation of humoral response after pertussis vaccination is immensely significant. In this study, compared to the positive control, the GC3111 group showed lower anti-FHA antibody level 2 weeks after booster vaccination, which was in line with the observations of a previous study [ 14 ]; however, the antibody response was comparable between the enhanced GC3111 group and the positive control group with respect to all antigens and all time points (Fig. 2 B).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, evaluation of humoral response after pertussis vaccination is immensely significant. In this study, compared to the positive control, the GC3111 group showed lower anti-FHA antibody level 2 weeks after booster vaccination, which was in line with the observations of a previous study [ 14 ]; however, the antibody response was comparable between the enhanced GC3111 group and the positive control group with respect to all antigens and all time points (Fig. 2 B).…”
Section: Discussionsupporting
confidence: 92%
“…Since 2000, a serological study in Korea has confirmed incidents of pertussis infection with higher certainty than reported earlier, and small-scale pertussis outbreaks have occurred once every 3 years since 2009, leading to the requirement for Tdap vaccination. In 2010, GC Pharma, a national company, started developing Tdap and DTaP vaccines; and our laboratory, the Vaccine Bio Research Institute, conducted animal-based studies [ 15 , 16 ] and performed clinical trials [ 14 ] using the Tdap booster vaccine. In animal studies, GC Pharma’s new Tdap vaccine, GC3111, was compared with Boostrix™, a commercially available product in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, evaluation of humoral response after pertussis vaccination is immensely signi cant. In this study, compared to the positive control, the GC3111 group showed a signi cantly lower anti-FHA antibody level 2 weeks after booster vaccination, which was in line with the observations of a previous study [13]; however, the antibody response was comparable between the enhanced GC3111 group and the positive control group with respect to all antigens and all time points (Fig. 2B).…”
Section: Discussionsupporting
confidence: 92%
“…Since 2000, a serological study in Korea has con rmed incidents of pertussis infection with higher certainty than reported earlier, and small-scale pertussis outbreaks have occurred once every 3 years since 2009, leading to the requirement for Tdap vaccination. In 2010, GC Pharma, a national company, started developing Tdap and DTaP vaccines; and our laboratory, the Vaccine Bio Research Institute, conducted animal-based studies [11,12] and performed clinical trials [13] using the Tdap booster vaccine. In animal studies, GC Pharma's new Tdap vaccine, GC3111, was compared with Boostrix™, a commercially available product in Korea.…”
Section: Discussionmentioning
confidence: 99%